1986
DOI: 10.1007/bf01209679
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and tissue responses to heavy ions: Basic considerations

Abstract: Responses of the S/S variant of the L5178Y murine leukemic lymphoblast, the photoreceptor cell of the rabbit retina and the lenticular epithelium of the rabbit to heavy ions (20Ne, 28Si, 40Ar and 56Fe) are described and discussed primarily from the standpoint of the need for a comprehensive theory of cellular radiosensitivity from which a general theory of tissue radiosensitivity can be constructed. The radiation responses of the very radiosensitive, repair-deficient S/S variant during the G1- and early S phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
3

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 13 publications
1
3
0
3
Order By: Relevance
“…An example of chromosome repair with normal and repair defective cells using high‐LET heavy ions is shown here 62. It has been shown that RBE reaches unity for cell killing in nonhomologous end joining (NHEJ) defective cells irradiated with high‐LET heavy ions 106–109. The cytogenetic difference was also greatly diminished between normal and NHEJ defective cells after high LET exposure 62.…”
Section: Premature Chromosome Condensation and Chromosome Repair Studiesmentioning
confidence: 99%
“…An example of chromosome repair with normal and repair defective cells using high‐LET heavy ions is shown here 62. It has been shown that RBE reaches unity for cell killing in nonhomologous end joining (NHEJ) defective cells irradiated with high‐LET heavy ions 106–109. The cytogenetic difference was also greatly diminished between normal and NHEJ defective cells after high LET exposure 62.…”
Section: Premature Chromosome Condensation and Chromosome Repair Studiesmentioning
confidence: 99%
“…For ionizing radiation, the RBE value increases with linear energy transfer (LET), peaks (around 100 − 200 keV/μm), and then decreases for DNA repair-proficient cells, whereas the RBE value constantly decreases with LET in repair-deficient cells [22, 23]. Neutrons with relatively high energy are classified as high-LET radiation, and it has been shown that neutrons have various high RBE values [4, 7, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Так, например, показано, что удаление бре шей репарационными механизмами происходит с полувременами 2; 15 и 160 мин [130]. В неделящихся клетках кролика восстановление поврежден ной ДНК до обычного размера хромосомы может занимать почти месяц [131]. Кинетика репарации поврежденных оснований может происходить с та кой же скоростью, как и репарация брешей [132,133].…”
Section: N6 -с6unclassified
“…Кинетика репарации поврежденных оснований может происходить с та кой же скоростью, как и репарация брешей [132,133]. Аналогичные времена жизни получены для дрожжей [131]. Характерные времена процессов, важных при образовании потенциальных мута ций, -это всегда доли секунды.…”
Section: N6 -с6unclassified